2017
DOI: 10.3390/ijerph14030234
|View full text |Cite
|
Sign up to set email alerts
|

Companion Animals and Child/Adolescent Development: A Systematic Review of the Evidence

Abstract: Childhood and adolescence are important developmental phases which influence health and well-being across the life span. Social relationships are fundamental to child and adolescent development; yet studies have been limited to children’s relationships with other humans. This paper provides an evidence review for the potential associations between pet ownership and emotional; behavioural; cognitive; educational and social developmental outcomes. As the field is in the early stages; a broad set of inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
209
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(241 citation statements)
references
References 81 publications
11
209
0
21
Order By: Relevance
“…With regard to children's pets, studies often have examined the development of empathy among children who nurture pets. Yet, as revealed in reviews, most of these studies do not treat dogs and cats separately, but rather lump dogs and cats together as companion animals or pets (4, 5), despite evidence that dogs and cats clearly differ (6). Often, dogs are emphasized as a major focus, perhaps because they frequently emerge as the preferred pet, as shown in an early study (7), and in examples from U.S. (8) and Holland (9).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to children's pets, studies often have examined the development of empathy among children who nurture pets. Yet, as revealed in reviews, most of these studies do not treat dogs and cats separately, but rather lump dogs and cats together as companion animals or pets (4, 5), despite evidence that dogs and cats clearly differ (6). Often, dogs are emphasized as a major focus, perhaps because they frequently emerge as the preferred pet, as shown in an early study (7), and in examples from U.S. (8) and Holland (9).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated that these pets can act as counselors, confidants, best friends (Black, 2009;Cassels et al, 2017;Griffin-Shirley & Nes, 2005;Zilcha-Mano et al, 2012), or even considered a sibling (Cassels et al, 2017). Additionally, pets offer unconditional love and acceptance (Brown, Richards, & Wilson, 1996;Hanselman, 2001;Piper, 2014;Purewal et al, 2017), the experience of accepting and receiving physical touch (Cassels et al, 2017;Fine, 2010;Piper, 2014), an attachment to an object (Cassels et al, 2017;Marsa-Sambola et al, 2017;Piper, 2014;Zilcha-Mano et al, 2012), or may encourage physical activity or health (Cloutier & Peetz, 2016;Winerman, 2017;Yam et al, 2012). Furthermore, pets have been found to assist in emotional well-being (Black, 2009;Brown et al, 1996;Chandler, 2012;Piper, 2014;Purewal et al, 2017;Zilcha-Mano et al, 2012) and recovery from physical illnesses (Beetz, Uvnäs-Moberg, Julius, & Kotrschal, 2012;Cloutier & Peetz, 2016;Kyngäs, 2004).…”
Section: Adolescents and Petsmentioning
confidence: 99%
“…According to Purewal et al (2017), several studies have demonstrated associations between adolescents' perspective taking, intellectual development, autonomy, and pet ownership. Purewal et al (2017) posit that pet ownership in adolescents correlates with increased social competence, social networks, social play behavior, and social interaction. Additionally, they state that as pets can give and receive affection, pets are able to contribute or somewhat fulfil adolescent attachment needs.…”
Section: Adolescents and Petsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, 41% of Canadian households owned at least one dog, and 37% owned at least one cat (Canadian Animal Health Institute, ). Animal companionship can have many physical and psychological benefits (Purewal et al, ); however, animals can also transmit zoonotic infections to people (Hoelzer, Switt, & Wiedmann, ). Humans can be exposed to zoonotic pathogens, including enteric pathogens, through animal bites or scratches, or contact with animals, their habitat, their waste or their food (Stull, Brophy, & Weese, ).…”
Section: Introductionmentioning
confidence: 99%